Deposition Time Effect on the Physical Properties of Cu2ZnSnS4 (CZTS) Thin Films Obtained by Electrodeposition Route onto Mo-coated Glass Substrates. (December 2015) - Tlemçani, Taoufik Slimani; Benamar, El Bachir; Moursli, Fouzia Cherkaoui El; Hajji, Faiza; Edfouf, Zineb; Taibi, Mhamed; Labrim, Hicham; Belhorma, Bouchra; Aazou, Safae; Schmerber, Guy; Bouras, Karima; Sekkat, Zouheir; et al.
Abstract: Kesterite Cu2 ZnSnS4 (CZTS) is a very promising absorber material for low cost and high efficiency thin film photovoltaic cells due to its direct band gap and to its high absorption coefficient. In this work, CZTS layers were deposited onto Mo-coated glass substrates using a single step electrodeposition process. Sulfurization treatment was performed under Argon atmosphere at 500 °C. The effect of the deposition time in the range of 10 min- 40 min was investigated. X-ray diffraction and Raman spectroscopy have confirmed the Kesterite structure of all deposited films. The surface morphology of the samples was examined using scanning electron microscopy. Cu/(Zn+Sn) of about 0.80, determined by energy dispersive X-ray spectroscopy, was reached for CZTS films electrodeposited during 30 min. Photoluminescence Spectroscopy showed a broad PL band centered around 1.45 eV.